Analisis Pengaruh Persepsi dan Konsep Hotel Syariah terhadap Minat Menginap di Hotel Syariah (Survey pada Masyarakat Kota Padangpanjang) - Nova, Siska Mitria; Qomarats, Izan; Ranelis, Ranelis; Washinton, Rahmad (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Muslims are a very potential market segment in the field of halal tourism. Halal tourism such as sharia hotels is a market opportunity that is very possible to be developed to meet the requirements of Muslim accommodation. However, the number of sharia hotels and visits to sharia hotels is less than conventional hotels, even though the number of Muslims in Indonesia is more dominant. This study aims to analyze the influence of perceptions and concepts of sharia hotels on the interest in staying in sharia-based hotels through a survey of the people of Padangpanjang City or the city of Serambi Mekah. To conduct the analysis, the technique used is quantitative with an exploratory research type. Sample collection with purposive sampling and 130 respondents. Data analysis using SPSS. The results of the study showed that r count> table so that all variables are valid. Cronbach Alpha coefficient> 0.70 so that all indicators are reliable. The results of the study showed that the perception and concept of sharia hotels have a positive effect on the interest in staying in the people of Padangpanjang City.